PEMODELAN SISTEM DAN ANALISIS KESTABILAN DINAMIK PESAWAT UAV (MODELING SYSTEM AND DYNAMIC STABILITY ANALYSIS OF UAV) - Purwanto, Eko Budi (BRIN Publishing, 2012)
Mission of Unmanned Aerial Vehicle (UAV) â€œElang Avionikâ€ is surveillance and aerial photographs. Therefore the flight of UAV must be stable and controlable, and first step activity is dynamic modelling and stability analisys. The problems of UAV system is disturbance, noise of sensor, MIMO and uncertainty dynamic model. For good result using the multivariable robust control, with some step research that is: (1)modeling and stability analysis, (2) design and implementation of PID control system, (3) flight dynamic parameter identification, (4) design and implementation of hardware in the loop simulation, (5) design and implementation of multivariable robust control, (6) test and evaluation of system. Simulation result show that the eigen value in longitudinal is: phugoid mode = â€“0,061293Â±0,40526i and non-oscillation mode = â€“6,1121Â±4,9253. In lateral directional is:dutch roll mode = â€“0,91089Â±5,7994i, spiral mode= â€“0,036563, and roll subsidence mode = â€“12,7181. Location of poles system on the left of imaginary axis, the means that the character of system is dynamic stable. But settling time to steady state condition is very long and improved by control system design.Key word: State space, Longitudinal, Lateral, Stable static, Stable dynamic